2021
DOI: 10.1101/2021.06.16.448737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unconventional conservation reveals structure-function relationships in the synaptonemal complex

Abstract: Functional requirements constrain protein evolution, commonly manifesting in conserved primary amino acid sequence. Here, we extend this idea to secondary structural features by tracking their conservation in essential meiotic proteins with highly diverged sequences. The synaptonemal complex (SC) aligns parental chromosome pairs and regulates exchanges between them. In electron micrographs of meiocytes from all eukaryotic clades, the SC appears as a ~100 nm-wide ladder-like structure with regular striations. D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…We inserted an HA epitope tag at the C-terminus of the endogenous coding sequence, and found that immunofluorescence with an epitope-specific antibody localized specifically between paired meiotic chromosomes, confirming SYP-4::HA as a useful marker for the SC (Figure 3A, B). A likely P. pacificus ortholog of C. elegans SYP-1 has also recently been identified, and an epitope-tagged allele displays an identical dynamic distribution (Kursel et al, 2021). The tagged SYP-4::HA protein supports normal meiosis, as indicated by the low percentage of inviable embryos and males among the progeny of homozygotes (Figure 3 -Supplement 1).…”
Section: Spo-11 and Dmc-1 Are Required For Homologous Synapsismentioning
confidence: 93%
“…We inserted an HA epitope tag at the C-terminus of the endogenous coding sequence, and found that immunofluorescence with an epitope-specific antibody localized specifically between paired meiotic chromosomes, confirming SYP-4::HA as a useful marker for the SC (Figure 3A, B). A likely P. pacificus ortholog of C. elegans SYP-1 has also recently been identified, and an epitope-tagged allele displays an identical dynamic distribution (Kursel et al, 2021). The tagged SYP-4::HA protein supports normal meiosis, as indicated by the low percentage of inviable embryos and males among the progeny of homozygotes (Figure 3 -Supplement 1).…”
Section: Spo-11 and Dmc-1 Are Required For Homologous Synapsismentioning
confidence: 93%